Harmless Acute Pancreatitis Score - Bharti, Shiv Vansh; Sharma, Anup (Journal of Nepalgunj Medical College, 2022)
Introduction: Acute Pancreatitis is a common disease in our region. It can range from mild to severe disease with high mortality rate. It is critical to identify patients who are at high risk for a severe disease course, since they require close monitoring and immediate aggressive treatment.Aims: To compare the effectiveness of Harmless Acute Pancreatitis Score with Ranson’s scoring system in predicting the severity of Acute Pancreatitis.Methods: A prospective cross sectional study was done among 45 patients who were admitted in surgery department over a period of one year with diagnosis of acute pancreatitis. If haematocrit was less than39% in female and less than43% in male, serum creatinine less than two miligram /deciliter and no sign of peritonitis, it was assigned as Harmless Acute Pancreatitis Score Zero. If at least one parameter was abnormal it was assigned as Harmless Acute Pancreatitis Score +. Severe pancreatitis (poor prognosis) was considered in those who required Intensive Care Unit care, who had in hospital mortality and who had hospitalization of more than five days. Patients with on admission Ranson’s score of more than three were suspected to have severe Pancreatitis.Results: There were total 45 patients, 18 females and 27 males. Twenty four patients were assigned as Harmless Acute Pancreatitis Score zero and 21 patients were assigned as Harmless Acute Pancreatitis Score +. Harmless Acute Pancreatitis Score was able to predict correctly in 18 out of 26 patients who fulfilled the criteria of poor prognosis (p